VD_FINDINFO HC / 2013 / 812 vom 10. Dezember 2013 - VD Tribunal cantonal (2013)
MESURE DE CONTRAINTEDROIT DES ÉTRANGERS, PROCÈS DEVENU SANS OBJET | 5 par. 1 let. f CEDH, 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr, 25 al. 1 LVLEtr, 30 LVLEtr, 31 LVLEtr